Readability of websites security privacy policies: A survey on text content and readers - Ali, Auwal Shehu; Zaaba, Zarul Fitri; Singh, Manmeet Mahinderjit; Hussain, Azham (Science and Engineering Research Support Society, 2020)
The aim of website's Privacy Policies is to educate consumers of a website's practices and procedures relating to their collection, usage, exchange, control, protection and the use of technology in relation to the information collection (website beacon and cookies) and transmission of user's personal information anytime he visits Internet website. This paper discusses a readability issues in privacy policies and how privacy scholars approach the issue. The paper also compares and analyzes research results on readability measurement of privacy policies and divides them into two categories according to different perspective. The perspective includes readability measurement from reader's perspective and readability measurement from privacy policies text content’s perspective. Our finding shows that website providers should give consumers better control regarding their information and give them more freedom in privacy policies. Only then will consumers become liberated from the burden of choosing between 2 unspeakable options. A legally binding document on the privacy policy can be written, that will also be clear and simple to read.